Challenges of health workers in primary health facilities in implementing obstetric emergency referrals to save women from death in Indonesia: A qualitative study - Novita Rudiyanti; Budi Utomo (Belitung Raya Foundation, 2024)
Background: One of the contributing factors to the high maternal mortality rate is the failure of the referral system, which inhibits the management of obstetric emergencies. Health workers at primary healthcare facilities serve as the gatekeepers of this referral system, and they must be equipped to make referral decisions, prepare referrals, and transport women safely and quickly to the hospital. Objective: This study aimed to explore the challenges faced by health workers in primary healthcare settings when implementing appropriate and rapid obstetric emergency referrals for women. Methods: A descriptive qualitative study design was employed, utilizing in-depth interviews with open-ended questions directed at 12 midwives working in health centers and private clinics in urban and rural areas from January to March 2024. The collected data were analyzed manually using content analysis. Results: Four themes were identified as challenges within the referral system: referral consent, pre-referral care ability, patient transfer to the hospital, and patient admission to the hospital. Factors that worsened the challenges for midwives in implementing obstetric emergency referrals were patients' perceptions of hospital care, the opinions of parents or family members, and levels of self-confidence. Additional factors included experience in emergency care, training, care guidelines, distance and travel time to the hospital, hospital refusals, patient handover mechanisms, and the attitudes of colleagues. Conclusion: Midwives, as health workers in primary healthcare, are expected to be skilled in addressing various challenges due to their close relationships with women at the forefront of the referral system. Enhancing competence in basic obstetric emergency care, improving communication between health facilities, and encouraging community empowerment are essential. Therefore, effective referrals from these improvements would enable women to receive timely and comprehensive obstetric emergency care. This study provides a foundational framework for developing interventions in health facilities and the community to strengthen the referral system and reduce maternal mortality in Indonesia.